Bankruptcy and Voluntary Liquidation: Evidence for New Firms in East and West Germany after Unification - Susanne Prantl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Exploiting the unique economic situation after German unification, I investigate how exit decisions deviate between new firms in a transition and a comparatively stable market environment. Two competing exit mechanisms are considered: entrepreneurial self-selection via voluntary liquidation and external selection based on insolvency regulation. Distinguishing between the competing exit modes proves to be crucial in semi-parametric propor- tional hazard-rate estimations. Comparing East and West Germany, I find distinct education and size effects and a higher share of bankruptcy-related liquidations in East Germany. These results are argued to reflect different industry structures, capital and labor market conditions in both parts of Germany.
Keywords: C14; L20; P30; P52; C41; 330; Exit; Bankruptcy; Voluntary Liquidation; Transition Economy; Duration Analysis; Marktaustritt; Liquidation; Konkurs; Unternehmensgründung; Vergleich; Alte Bundesländer; Neue Bundesländer; Deutschland